Traveller infant mortality is persistently higher than the general population in the All Ireland Traveller Birth Cohort study. (13th September 2011) - Hamid, NA*; Kelleher, C; Fitzpatrick, P
Abstract : Introduction: Irish Travellers are a nomadic minority group on the island of Ireland (IOI). The All Ireland Traveller Health Study (2010) showed inequalities in socioeconomic and health indicators. The infant mortality rate (IMR) in 1987 was 18.1 (95% CI 10.9 to 25.3) per 1000 births, one of the highest in Europe. The aim of this study was to calculate the IMR, neonatal mortality rate (NMR) and postneonatal mortality rate (PNMR) for Ireland Travellers, to compare with the general Irish population, and to describe major causes of death. Methodology: The Traveller birth cohort study comprises all Traveller babies born between 14 October 2008 and 13 October 2009 (n=986) on IOI and followed up over 1 year. Cohort ascertainment strategies to estimate infant mortality included data collected through public health nurses (PHNs), Traveller health projects (THPs), mass media such as parish newsletter and Traveller-specific social magazines. A comprehensive search for death certificates was performed in the General Register Office with confirmation of Traveller status sought from PHNs/THPs. Results: 12 infant deaths were identified in IOI based on cohort period, including 1 death from Northern Ireland. Some deaths were not officially registered. Using capture-recapture technique, an estimated true range of infant deaths was calculated as 10 to 15 cases. Congenital anomalies (n=5), preterm births (n=2), metabolic diseases (n=4) and accidents (n=1) are the leading causes of death. The cohort IMR for ROI Travellers was 12.0 (95% CI 5.5 to 19.7), 3.7 times the general population IMR 3.2 (92% CI 3.22 to 3.24) and 2.7 times the European average in 2008. The ROI Traveller NMR was 5.4 (95% CI 5.3 to 5.6), almost twice the 2008 European average, compared to 2.27 (95% CI 2.26 to 2.29) for the general Irish population and 14.4 (95% CI 14.1 to 14.7) for Travellers in 1987. PNMR increased by 180% from 3.6 (95% CI 3.4 to 3.8) in 1987 to 6.5 (95% CI 6.4 to 6.7) in 2009; for general Irish population in 2009, the PNMR was 0.95 (95% CI 0.95 to 0.96). Conclusion: There has been some improvement in Traveller infant mortality over two decades, however the greater improvement in the general population results in a widening gap. Improvement in neonatal care has shifted previous neonatal deaths to the postneonatal period. The raised infant mortality is not associated with factors related to adverse social conditions, a positive finding.